RAY TRACING RENDER MENGGUNAKAN FRAGMENT ANTI ALIASING - Febriliyan Samopa; Wawan Mardian (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2008)
Rendering is generating surface and three-dimensional effects on an object displayed on a monitor screen. Ray tracing as a rendering method that traces ray for each image pixel has a drawback, that is, aliasing (jaggies effect). There are some methods for executing anti aliasing. One of those methods is OGSS (Ordered Grid Super Sampling). OGSS is able to perform aliasing well. However, this method requires more computation time since sampling of all pixels in the image will be increased. Fragment Anti Aliasing (FAA) is a new alternative method that can cope with the drawback. FAA will check the image when performing rendering to a scene. Jaggies effect is only happened at curve and gradient object. Therefore, only this part of object that will experience sampling magnification. After this sampling magnification and the pixel values are computed, then downsample is performed to retrieve the original pixel values. Experimental results show that the software can implement ray tracing well in order to form images, and it can implement FAA and OGSS technique to perform anti aliasing. In general, rendering using FAA is faster than using OGSS although there is some situation where the time effectiveness is equal. This is possible since the process of intersection searching on FAA needs additional time. Rendered images using FAA are relatively similar to those using OGSS. Kata Kunci: Ray Tracing, Fragment Anti Aliasing, Ordered Grid Super Sampling, Render, Sampling, Jaggies